Cybersecurity in maritime logistics : trends, opportunities and challenges in people - Lai, Nicole (2019)
Cyber security has become an international priority. With hackers and criminals lurking online, the most fearsome pirates aren’t the ones at sea but online. We would be exploring how the people element plays a huge role in maritime cyber security. We would be investigating the trends, opportunities and challenges to cyber security posed by human weaknesses, behaviour and psychology. We conducted our hypothesis testing over surveys and interview while, analysing our results via the IBM SPSS tool. We have found that an orientation for collectivism and uncertainty avoidance of the Hofstede’s cultural dimensions could potentially decrease or increase their company’s potential for cyber security via their effect on the four factors: company’s commitment to cyber security, company’s cyber security proactivity, employee’s reliance on their IT department and their receptiveness of the different factors of established technological acceptance model. We also did further research on how people’s cyber security awareness would affect a maritime organisation’s potential for cyber risk. The report further explains how to potentially mitigate the negative effects of each culture in the research implications.